Phylogeny of Miliusa (Magnoliales: Annonaceae: Malmeoideae: Miliuseae), with descriptions of two new species from Malesia - Chaowasku, Tanawat; Keßler, Paul J.A. (European Journal of Taxonomy, 2013)
The molecular phylogeny of Miliusa (Annonaceae) is reconstructed, with 27 (of ca. 50) species included, using a combination of seven plastid markers (rbcL exon, trnL intron, trnL-F spacer, matK exon, ndhF exon, psbA-trnH spacer, and ycf1 exon) constituting ca. 7 kb. In addition, two new species of Miliusa are described from the Malesian area: M. butonensis sp. nov. from Buton Island, Indonesia and M. viridiflora sp. nov. from Papua New Guinea. The former is included in the molecular phylogenetic analysis. The reconstructed phylogeny corresponds well to the informal morphological grouping proposed earlier. A revised key to 13 Austro-Malesian species of Miliusa is provided.